Experts Consensus on Diagnosis and Treatment of Autoinflammatory Diseases - The Subspecialty Group of Rheumatology,the Society of Pediatrics, Chinese Medical Association; The Pediatric Group of Chinese Medical Doctor Association Committee on Rheumatology and Immunology; The Pediatric Group of Rheumatology and Immunology Professional Committee of Cross Strait Medical and Health Exchange Association; Immunology Professional Committee of Futang Children's Medical Development Research Center (罕见病研究, 2022)
Autoinflammatory diseases(AIDs) are a group of diseases caused by gene mutations that change coding proteins, leading to the imbalance of innate immune system and leads to systemic inflammatory response. This group of diseases is characterized by repeated or continuous inflammatory response(increased acute phase inflammatory protein) and lack of synergy of the adaptive immune system(lack of autoreactive T cells and autoantibodies). AIDs have a wide variety of clinical manifestations and pathogenesis. They can be divided into different types according to clinical characteristics and pathogenesis. For patients with a young onset age, the possibility of AIDs should be considered if manifestations of recurrent fever in addition to other systemic inflammatory manifestations are seen, along with family history. It is clear that the diagnosis depends on the comprehensive analysis of medical history, clinical manifestations and gene test results. Drugs for the treatment of AIDs include non-steroidal anti-inflammatory drugs, glucocorticoids, immunosuppressants and biological agents. Early diagnosis and active treatment of AIDs can effectively reduce systemic inflammation, alleviate organ injury and reduce the incidence of long-term complications. In order to standardize the diagnosis and treatment of AIDs, the Subspecialty Group of Rheumatology, the Society of Pediatrics, Chinese Medical Association specially formulated the experts consensus on the diagnosis and treatment of AIDs.